2022
DOI: 10.1002/ab.22021
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress mediates the connection between sleep deprivation and physical fighting in adolescents

Abstract: Lack of sleep is common in adolescence, and represents an important threat to adolescents' well-being, academic commitment, and general health. It also has significant behavioral consequences through an increased likelihood of interpersonal violence. Previous studies have demonstrated an association between aggressive behavior and lack of sleep, but the psychological mediators remain completely unexplored. Grounded in the General Aggression Model, we investigated the affective pathway as one of the potential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…Todos los estudios que llevaron a cabo análisis correlaciones sin manipulación de variables seleccionados encontraron asociaciones significativas entre algunas de sus respectivas medidas del sueño y de la conducta agresiva. Así, 4 de estos estudios evaluaron de manera exclusiva la duración del sueño y encontraron que la falta de sueño se asociaría con la agresión física (Bègue et al, 2022;Street et al, 2016), la agresión en el ámbito laboral (Osgood et al, 2021) y las peleas físicas (Soares et al, 2019). Además, dos de estos estudios pusieron de manifiesto que ciertas variables podrían mediar dicha asociación entre un sueño insuficiente y la conducta agresiva.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Todos los estudios que llevaron a cabo análisis correlaciones sin manipulación de variables seleccionados encontraron asociaciones significativas entre algunas de sus respectivas medidas del sueño y de la conducta agresiva. Así, 4 de estos estudios evaluaron de manera exclusiva la duración del sueño y encontraron que la falta de sueño se asociaría con la agresión física (Bègue et al, 2022;Street et al, 2016), la agresión en el ámbito laboral (Osgood et al, 2021) y las peleas físicas (Soares et al, 2019). Además, dos de estos estudios pusieron de manifiesto que ciertas variables podrían mediar dicha asociación entre un sueño insuficiente y la conducta agresiva.…”
Section: Resultsunclassified
“…Además, dos de estos estudios pusieron de manifiesto que ciertas variables podrían mediar dicha asociación entre un sueño insuficiente y la conducta agresiva. Por un lado, Bègue et al (2022) concluyeron que el malestar/sufrimiento psicológico constituiría una variable intermediaria entre una cantidad insuficiente de sueño y la conducta agresiva en adolescentes, la cual mediaría parcialmente el efecto de la falta de sueño sobre la agresión física. Por otro lado, Osgood et al (2021) informaron de que la escasa duración y la discontinuidad del sueño se asociarían con más agresión en el contexto laboral de los militares, y que esta influencia sería ejercida en parte a través de procesos de depresión, ansiedad, estrés postraumático, y, especialmente, el rasgo de ira.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The relationships between aggressive emotions and PTSD symptoms as well as psychological distress are plausible. Aggressive feelings are possible symptoms according to the DSM 5 criteria for PTSD [33] and are associated with high levels of psychological distress [34]. Earlier studies showed that orientation toward PN is positively related to PTSD symptoms [66].…”
Section: Discussionmentioning
confidence: 99%
“…Aggression, irritability, or destructive behaviors are possible symptoms according to DSM 5 criteria for PTSD [33]. In addition to traumatic experiences and distorted time perspectives, a lack of sleep, which is common in individuals suffering from PTSD, as well as high psychological distress may foster aggressive feelings and aggressive behaviors [34]. Adolescent refugees suffer, on average, from increased psychological distress, which may be attributed to post-migration stressors [31].…”
Section: Introductionmentioning
confidence: 99%